An Improved FPGA Implementation of Direct Torque Control for Induction Machines - Sutikno, Tole; Nik Idris, Nik Rumzi; Jidin , Auzani; Marcian, N. Cirstea (2013)
This paper presents a novel direct torque control (DTC) approach for induction machines, based on an improved torque and stator flux estimator and its implementation using field-programmable gate arrays (FPGA). The DTC performance is significantly improved by the use of FPGA, which can execute the DTC algorithm at higher sampling frequency. This leads to the reduction of the torque ripple and improved flux and torque estimations. The main achievements are: 1) calculating a discrete integration operation of stator flux using backward Euler approach; 2) modifying a so called nonrestoring method in calculating the complicated square root operation in stator flux estimator; 3) introducing a new flux sector determinationmethod; 4) increasing the sampling frequency to 200 kHz such that the digital computation will perform similar to that of the analog operation; and 5) using two’s complement fixed-point format approach to minimize calculation errors and the hardware resource usage in all operations. The design was achieved in VHDL, based on a MATLAB/Simulink simulation model. The Hardware-in-the-Loop method is used to verify the functionality of the FPGA estimator. The simulation results are validated experimentally. Thus, it is demonstrated that FPGA implementation of DTC drives can achieve excellent performance at high sampling frequency.